Long-term Systemic Metal Distribution in Patients With Stainless Steel Spinal Instrumentation: A Case-Control Study. Issue 3 (April 2015) - Savarino, Lucia; Greggi, Tiziana; Martikos, Konstantinos; Lolli, Francesco; Greco, Michelina; Baldini, Nicola
Abstract : Study Design: Case-control study. Objective: To verify whether metal ions in the serum of patients bearing spinal stainless steel instrumentation were elevated over the long-term period after implantation of stainless steel prostheses and to determine whether these levels could predict potential unfavorable outcomes. Summary of Background Data: Instrumented spinal arthrodesis, the standard procedure to correct scoliosis, routinely remains in situ for the lifetime of the patient. Elevated metal ion levels have been reported at short-term follow-up, but the long-term status, possibly related to systemic toxic effects, is unknown. Methods: Twenty-two patients treated for scoliosis with posterior spinal arthrodesis using stainless steel instrumentation were included. Minimum follow-up was 10 years. Oswestry Disability Index and visual analog scale were recorded. Chromium (Cr) and nickel (Ni) levels were measured (ng/mL) and compared with levels in a control group including 30 healthy subjects. A receiver-operating characteristic curve was calculated on the basis of the clinical assessment (pain and disability) and the x-ray picture; the cutoff values for the parameters were settled, and the ion-testing potential was considered as a surrogate marker for failure. Results: The level of Cr was significantly increased in patients, compared with controls ( P =0.018). A remarkable Cr release without any clinical-radiologic sign was recorded in some female patients. A high specificity (93%), positive likelihood ratio (7.00), and overall accuracy (77%) were calculated for Cr; these indicate a high risk of failure when the levels exceeded the cutoff value, which was 0.6 ng/mL. No significant difference between the groups was found for Ni ( P =0.7). Conclusions: Cr testing is suggested as a reliable marker for the malfunctioning assessment and as a support for standard procedures, especially with doubtful diagnosis. Furthermore, high levels of Cr ions were observed in female patients. This finding deserves attention especially when counseling young fertile women.